How Should We Develop the Careers of Our Employees? Organizational Career Management Tools in Focus - Karoliny, Martonné; Bálint, Brigitta; Galambosné Tiszberger, Mónika (International Journal of Engineering and Management Sciences, 2016)
We can observe more and more often that people change their jobs frequently. They work for more employers during their life. The question may arise that organizations should care about the career management of their workers? Certain surveys which investigate the reasons of job changes can disprove it. One of the most common causes is that employees cannot see their career opportunities at the company. The organizations should not necessarily use complex career development systems it may also be appropriate, if they use only some techniques consciously. The study shows the career management tools used by the organizations examined in the survey. The authors demonstrate that there is a provable relation between organizational performance and career development methods. Furthermore they describethe techniques applied by the successful organizations.